## Tag `081I`

Chapter 28: Morphisms of Schemes > Section 28.24: Flat morphisms

Lemma 28.24.15. Let $f : X \to Y$ be a flat morphism of schemes. Let $g : V \to Y$ be a quasi-compact morphism of schemes. Let $Z \subset Y$ be the scheme theoretic image of $g$ and let $Z' \subset X$ be the scheme theoretic image of the base change $V \times_Y X \to X$. Then $Z' = f^{-1}Z$.

Proof.Recall that $Z$ is cut out by $\mathcal{I} = \mathop{\rm Ker}(\mathcal{O}_Y \to g_*\mathcal{O}_V)$ and $Z'$ is cut out by $\mathcal{I}' = \mathop{\rm Ker}(\mathcal{O}_X \to (V \times_Y X \to X)_*\mathcal{O}_{V \times_Y X})$, see Lemma 28.6.3. Hence the question is local on $X$ and $Y$ and we may assume $X$ and $Y$ affine. Note that we may replace $V$ by $\coprod V_i$ where $V = V_1 \cup \ldots \cup V_n$ is a finite affine open covering. Hence we may assume $g$ is affine. In this case $(V \times_Y X \to X)_*\mathcal{O}_{V \times_Y X}$ is the pullback of $g_*\mathcal{O}_V$ by $f$. Since $f$ is flat we conclude that $f^*\mathcal{I} = \mathcal{I}'$ and the lemma holds. $\square$

The code snippet corresponding to this tag is a part of the file `morphisms.tex` and is located in lines 4490–4496 (see updates for more information).

```
\begin{lemma}
\label{lemma-flat-base-change-scheme-theoretic-image}
Let $f : X \to Y$ be a flat morphism of schemes. Let $g : V \to Y$ be a
quasi-compact morphism of schemes. Let $Z \subset Y$ be the scheme theoretic
image of $g$ and let $Z' \subset X$ be the scheme theoretic image of the
base change $V \times_Y X \to X$. Then $Z' = f^{-1}Z$.
\end{lemma}
\begin{proof}
Recall that $Z$ is cut out by
$\mathcal{I} = \Ker(\mathcal{O}_Y \to g_*\mathcal{O}_V)$
and $Z'$ is cut out by
$\mathcal{I}' = \Ker(\mathcal{O}_X \to
(V \times_Y X \to X)_*\mathcal{O}_{V \times_Y X})$, see
Lemma \ref{lemma-quasi-compact-scheme-theoretic-image}.
Hence the question is local on $X$ and $Y$ and we may assume $X$ and $Y$
affine. Note that we may replace $V$ by $\coprod V_i$ where
$V = V_1 \cup \ldots \cup V_n$ is a finite affine open covering.
Hence we may assume $g$ is affine. In this case
$(V \times_Y X \to X)_*\mathcal{O}_{V \times_Y X}$ is the pullback
of $g_*\mathcal{O}_V$ by $f$. Since $f$ is flat we conclude that
$f^*\mathcal{I} = \mathcal{I}'$ and the lemma holds.
\end{proof}
```

## Comments (0)

## Add a comment on tag `081I`

Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like `$\pi$`

). A preview option is available if you wish to see how it works out (just click on the eye in the lower-right corner).

All contributions are licensed under the GNU Free Documentation License.

There are no comments yet for this tag.

There is also 1 comment on Section 28.24: Morphisms of Schemes.